The Prospective Role of Plant Products in Radiotherapy of Cancer: A Current Overview - Hazra, Banasri; Ghosh, Subhalakshmi; Kumar, Amit; Pandey, B. N. (Frontiers in Pharmacology, 2012)
Treatment of cancer often requires exposure to radiation, which has several limitations involving nonspecific toxicity toward normal cells, and development of resistance to treatment. Efforts are going on to find chemical compounds which would effectively offer protection to the normal tissues after radiation exposure during radiotherapy of cancer. In this regard, plant-derived compounds might serve as ‘leads’ to design ideal radioprotectors/ radiosensitisers. This article reviews some of the recent findings on prospective medicinal plants, phytochemicals and their analogues, based on both in vitro and in vivo tumor models especially focused with relevance to cancer radiotherapy. Also, pertinent discussion has been presented on the molecular mechanism of apoptotic death in relation to the oxidative stress in cancer cells induced by some of these plant samples and their active constituents.